La amada roña: memoria urbana en la obra de Franco - Lostra, Agustín César (2018)
This is an essay about the work of the Colombian photographer Fernell Franco (1942-2006) which arises from its association with the concepts of memory and dirt. It analyzes how peculiarly it highlights a socialhistorical process that defines us as Latin Americans: the Eurocentric progress breaking the entire essence of our cities. It outlines the contrast between an aseptic esthetic horizon connected to the hegemonic esthetic oppression and a protection of the filthy as resistance to what is forgotten for being old fashioned, non productive.